A unique assemblage of epibenthic sessile suspension feeders with archaic features in the high-Antarctic - Gili, Josep Maria; Arntz, Wolf E.; Palanques, Albert; Orejas, Covadonga; Clarke, Andrew; Dayton, Paul K.; Isla, Enrique; Teixidó, Nuria; Rossi, Sergio; López-González, Pablo J. (Deep Sea Research Part II: Topical Studies in Oceanography, 2006)
Special issue EASIZ: Ecology of the Antarctic Sea Ice Zone. Ecology of the Antarctic Sea Ice Zone: Final Symposium.-- 24 pages, 4 figures We suggest that the epibenthic communities of passive suspension feeders that dominate some high-Antarctic seafloors present unique archaic features that are the result of long isolation, together with the effects of environmental features including reduced terrestrial runoff and favourable feeding conditions. These features probably originated during the Late Cretaceous, when the high-Antarctic environment started to become different from the surrounding oceans. Modern Antarctic communities are thus composed of a mixture of Palaeozoic elements, taxa that migrated from the deep ocean during interglacial periods, and a component of fauna that evolved from common Gondwana Cretaceous ancestors. We explore this hypothesis by revisiting the palaeoecological history of Antarctic marine benthic communities and exploring the abiotic and biotic factors involved in their evolution, including changes in oceanic circulation and production, plankton communities, the development of glaciation, restricted sedimentation, isolation, life histories, and the lack of large predators. The conditions favouring the retention of apparently archaic features in the Antarctic marine fauna remain to be fully elucidated, but high-Antarctic communities are clearly unique and deserve special conservation Financial support was provided by MCYT Grants (Spanish Antarctic Research Programme; REN2000-3096-E/ANT, REN2003-04236) Peer reviewed